The role of transaction costs in the delivering of urban infrastructure services: an overview of brazilian and portuguese municipalities - Lucca, Paulo Vitor (2020)
The present paper explores the different options for delivering public services by Portuguese and Brazilian municipalities. With reduction of human and financial resources and increase in demand, large municipalities need efficient arrangements to deliver public services. In fact, the conditions for providing these services influence the quality of life, the economic development and are directly related to the capacity of institutions to find the most appropriate governance mechanisms. In this context, the use of Transaction Costs Theory (TCT), specifically economic and political costs, reveals an appropriated tool to understand the ways how public services can be delivered. Existing research and theory point out several studies around the world that analyze how different governance mechanism’s choice (hierarchy, market and network) can be explained based on TCT. This paper contributes to expand this topic to Brazilian’s municipalities context, due to the lack of studies in this country. Contrariwise, there are more studies about Portuguese’s municipalities, but as a dynamic process, it’s becomes interesting update such studies in order to expand the existing database. In this sense we addressed a preliminary step whose objective is to identify the different options for public service delivery, finding similarities and differences in these two countries, following a qualitative approach. As results, we find that governance mechanisms adopted by two countries are very similar. The differences result from regional level in Brazil that allows recourse to state's business sector, as opposed to Portugal. In turn, Portuguese municipalities have several options that result from municipal associations, options that are more limited in Brazilian case.